Disrupting galectin-1 interactions with N-glycans suppresses hypoxia-driven angiogenesis in Kaposi's sarcoma - Croci Russo, Diego Omar (2012)
Kaposi’s sarcoma (KS), a multifocal vascular neoplasm linked to human herpesvirus-8 (HHV-8/KS-associated herpesvirus [KSHV]) infection, is the most common AIDS-associated malignancy. Clinical management of KS has proven to be challenging because of its prevalence in immunosuppressed patients and its unique vascular and inflammatory nature that is sustained by viral and host-derived paracrine-acting factors primarily released under hypoxic conditions. We show that interactions between the regulatory lectin galectin-1 (Gal-1) and specific target N-glycans link tumor hypoxia to neovascularization as part of the pathogenesis of KS. Expression of Gal-1 is found to be a hallmark of human KS but not other vascular pathologies and is directly induced by both KSHV and hypoxia. Interestingly, hypoxia induced Gal-1 through mechanisms that are independent of hypoxia-inducible factor (HIF) 1α and HIF-2α but involved reactive oxygen species–dependent activation of the transcription factor nuclear factor κB. Targeted disruption of Gal-1–N-glycan interactions eliminated hypoxia-driven angiogenesis and suppressed tumorigenesis in vivo. Therapeutic administration of a Gal-1–specific neutralizing mAb attenuated abnormal angiogenesis and promoted tumor regression in mice bearing established KS tumors. Given the active search for HIF-independent mechanisms that serve to couple tumor hypoxia to pathological angiogenesis, our findings provide novel opportunities not only for treating KS patients but also for understanding and managing a variety of solid tumors.